ENERGY AUDIT OF TECHNOLOGICAL EQUIPMENT IN SOFT DRINK MANUFACTURING: ASSESSMENT AND OPTIMIZATION FOR EFFICIENCY AND SUSTAINABILITY - Shaislamov Alisher Shabdurahmanovich; Mukhamadiyev Shakhzod Ravshan ogli (Modern American Journals, 2026)
Energy management is a critical component in soft drink manufacturing due to the high energy intensity of production processes and the growing emphasis on sustainable operations. Soft drink factories operate with a range of technological equipment, including mixers, pasteurizers, carbonation units, bottling and packaging lines, refrigeration systems, pumps, and auxiliary devices, all of which consume substantial amounts of electricity, steam, and compressed air. Inefficient energy usage results in increased operational costs, reduced equipment lifespan, and heightened environmental impact. Conducting comprehensive energy audits provides insight into energy flows, identifies inefficiencies, and facilitates the development of strategies for optimization. This article examines the energy characteristics of technological equipment in soft drink production, details methodologies for energy audits, and explores measures to enhance energy efficiency, including automation, heat recovery, equipment modernization, and AI-assisted monitoring, highlighting the economic, operational, and environmental benefits for sustainable beverage production.
Keywords: Energy Audit, Soft Drink Manufacturing, Technological Equipment, Energy Efficiency, Industrial Automation, Sustainability.